1605d Correlating biological monitoring for platinum with dermal and respiratory exposure. (24th April 2018) - Plessis, Johan du
Abstract : Introduction: Occupational respiratory exposure to platinum is well established in precious metals refineries (PMR). Soluble platinum causes respiratory sensitisation leading to amongst others occupational asthma and rhinitis. However, several skin symptoms have been reported and the relationship between skin exposure and uptake determined in urine has not been investigated. Objectives: To evaluate the dermal and respiratory exposure of PMR workers to soluble platinum, and to quantify the absorbed platinum concentration excreted via the urine. Methods: Dermal exposure samples were collected on the dominant palm, wrist, neck and forehead using Ghostwipes. Respiratory samples were collected using an Institute of Occupational Medicine inhalable aerosol sampler. Wipe and respiratory samples were analysed according to the MDHS 46/2 using inductively coupled plasma-mass spectrometry. The dermal and respiratory exposures of workers from different production areas in two PMRs were measured simultaneously on two consecutive days. Urine samples were collected on the morning of the first day and on the two following mornings. Results: The degree of dermal and respiratory exposure varied considerably between workers working in different areas of the refineries. Most workers experienced dermal and respiratory exposure to soluble platinum above the detection limit (0.005 µg) with 25% of the respiratory exposures exceeding the national 8 hour occupational exposure limit of 2 µg/m3. Dermal exposure (average of anatomical positions) were ≤6.79 µg/cm2. Urine platinum concentrations ranged between <0.1 and 3 µg/g creatinine. Statistically significant positive correlations were established for: (i) average dermal exposure and average respiratory exposure, (ii) average dermal exposure and average platinum urinary concentration, and (iii) average respiratory exposure and average platinum urinary concentration. Discussion: The concentration platinum in the urine of workers is determined by both the dermal and respiratory exposure routes. The skin is as a route of exposure to soluble platinum should be considered.